If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 = c + -5 Reorder the terms: -18 = -5 + c Solving -18 = -5 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. -18 + -1c = -5 + c + -1c Combine like terms: c + -1c = 0 -18 + -1c = -5 + 0 -18 + -1c = -5 Add '18' to each side of the equation. -18 + 18 + -1c = -5 + 18 Combine like terms: -18 + 18 = 0 0 + -1c = -5 + 18 -1c = -5 + 18 Combine like terms: -5 + 18 = 13 -1c = 13 Divide each side by '-1'. c = -13 Simplifying c = -13
| -2(7x+1)=14-6x | | 200=xl | | x=35313(35313*0.16) | | 6z+7=5z+6 | | 400/460 | | m-(-18)=7 | | -5x-4-5x=-24 | | 7-3y+6=-7 | | 9=5+2g | | -4(6n-4)-7= | | ax^2-bx^2=0 | | 16+c=-5 | | 1+4a-a= | | 15y+3x=61 | | 0=-16t^2+24t+40 | | 4+2q=8 | | 5n+3=4-6(6-5n) | | p+(-9)=8 | | 10=3y+1 | | -14-8k=2k+8k | | 3x=x^2+9 | | 50=x(x*0.16) | | -12+5m+10=2m-10-m | | (15/28)/35 | | t/7=-9/1 | | 8r-5q=3forq | | -d+7= | | 13x+1+12x+9= | | t/t=-9/1 | | 10x-4-6x=-84 | | 9x-81=7 | | .3+.6=.06 |